PRL-secreting pituitary adenomas in pregnancy - Chiodini, Iacopo; Liuzzi, A. (Journal of endocrinological investigation, 2003)
Dopamine-agonists have significantly increased the number of pregnancies in women with micro- and macro-prolactinomas, as ovulation can be restored in the great majority of these patients. Thus, the main questions regard the possible consequences of high estrogen levels on tumor volume and the possible effects of D2-agonists on fetal development. While the risk of tumor increase is low in patients with prolactin secreting micro-adenoma (MIP), in PRL secreting macro-adenoma (MAP) patients the possibility of tumor growth is enhanced and influenced by previous treatment. Moreover, while it is well known that the exposition for only the first 4 weeks to bromocriptine (BRC) therapy does not affect the outcome of pregnancy, data on the use of BRC during the whole gestation are limited to just over 100 cases. Female pregnant patients with MIP, therefore, must be reassured and medical therapy suspended, with successive clinical follow-up. In the case of pregnant MAP subjects, the best approach from pre-pregnancy debulking, dopamine-agonist therapy interruption and BRC therapy continuation must be agreed on with the patient, and a careful follow-up instituted.